The Relationship Between Knowledge Level and Prevention of NT Type DM Complications at Perdagangan Hospital, Simalungun Regency - Doortua; Romauli Pakpahan; Josep Lubis; Ratna Juwita Laila; Deby Saprianti Damanik (International Journal of Public Health Excellence (IJPHE), 2022)
Diabetes Mellitus (DM) is a collection of symptoms that arise in a person caused by an increase in blood glucose levels due to a progressive decrease in insulin secretion against the background of insulin resistance. The prevalence of diabetes mellitus is always increasing every year. This increase is inseparable from the lifestyle that is being lived by the world's population today. This research is descriptive in nature. This study aims to describe the behavior of type II diabetes mellitus patients in preventing complications of diabetes mellitus in the working area of the Trading Health Center in 2021. Sampling in this study using fatal sampling, namely 33 respondents who suffer from type II DM. Of the 33 respondents, 16 respondents (49%) were aged 51-60 years, the majority were female, 21 respondents (64%), the majority had high school education, 13 respondents (40%), and the majority had diabetes for a long time, namely 1-4. years as many as 29 respondents (88%). The results showed that of the 33 respondents who visited the Commercial Health Center in 2021, the majority had good knowledge as many as 22 respondents (67%), the majority had a positive attitude as many as 21 respondents (64%), and the majority had bad behavior as many as 22 respondents (67 % ). It is hoped that the community will further improve behavior regarding diabetes mellitus in order to avoid or prevent complications that can arise from diabetes mellitus.